Effects of Drip Irrigation Frequency on Emitter Clogging using Saline Water for Processing Tomato Production†. (7th February 2019) - Lili, Zhangzhong; Peiling, Yang; Wengang, Zheng; Yu, Liu; Mengji, Guo; Fengru, Yang
Abstract: As an important parameter of drip irrigation using saline water, irrigation frequency not only affects crop growth by changing the soil moisture–salinity distribution, but also influences the anti‐clogging performance of the drip irrigation system by changing fouling growth inside emitters. Hence, a representative medium‐salt‐tolerant crop of processing tomatoes was selected as the research object. The effects of different drip irrigation frequencies (S1 (1‐day irrigation interval), S2 (2‐day irrigation interval) and S3 (4‐day irrigation interval)) on the clogging characteristics of emitters were analysed via a 2‐year drip irrigation experiment using saline water between 2013 and 2014. The results showed that the discharge ratio variation (Dra) and the Christiansen uniformity coefficient (CU) of the emitters decreased as the irrigation interval increased, while there was a negative linear correlation between Dra and the irrigation interval ( R 2 > 0.79). The highest Dra and CU values of 80.9 and 78.0% were observed in high‐frequency irrigation (S1) after 2 years of planting. Moreover, clogging fouling inside the emitter accumulated gradually and exhibited a significant positive linear correlation with irrigation interval time ( R 2 > 0.80). The chemical components of clogging fouling, which were calcium magnesium carbonates, quartz, silicates, and sodium chloride, were the same under different irrigation frequencies. The emitter clogging of drip irrigation systems using saline water for processing tomato production in the Hetao irrigation area presented a composite clogging (mainly chemical clogging associated with physical clogging). Considering previous research, a high frequency of once per day is recommended for drip irrigation using saline water. © 2019 John Wiley & Sons, Ltd. Résumé: En tant que paramètre important de l'irrigation goutte‐à‐goutte avec des eaux salées, la fréquence d'irrigation influe non seulement sur la croissance des cultures en modifiant la distribution humidité–salinité du sol, mais aussi sur les performances anti‐colmatage du système d'irrigation goutte‐à‐goutte en modifiant la croissance de l'encrassement à l'intérieur des émetteurs. Par conséquent, une culture de tomates de transformation, tolérante à des teneurs moyennes de sel, a été choisie comme objet de recherche. Les effets des différentes fréquences d'irrigation au goutte à goutte (S1 (intervalle d'irrigation de 1 jour), S2 (intervalle d'irrigation de 2 jours) et S3 (intervalle d'irrigation de 4 jours)) sur les caractéristiques de colmatage des émetteurs ont été analysés via une expérience de deux ans utilisant des eaux salées entre 2013 et 2014. Les résultats ont montré que la variation du rapport de débit (Dra) et le coefficient d'uniformité de Christiansen (CU) des émetteurs diminuaient à mesure que l'intervalle d'irrigation augmentait, alors qu'il existait une corrélation négative linéaire entre Dra et l'intervalle d'irrigation ( R 2 > 0.79). Les valeurs les plus élevées de Dra et CU de 80.9 et 78.0% ont été observées dans l'irrigation à haute fréquence (S1) après deux ans de plantation. De plus, l'encrassement à l'intérieur de l'émetteur s'accumulait progressivement et présentait une corrélation positive linéaire significative avec l'intervalle d'irrigation ( R 2 > 0.80). Les composants chimiques de l'encrassement, qui étaient des carbonates de calcium‐magnésium, du quartz, des silicates et du chlorure de sodium, étaient les mêmes pour les différentes fréquences d'irrigation. Le colmatage de l'émetteur des systèmes d'irrigation goutte‐à‐goutte utilisant de l'eau saline pour la production de tomates de transformation dans la zone d'irrigation de Hetao présentait un colmatage composite (principalement un colmatage chimique associé à un colmatage physique). Compte tenu des recherches précédentes, une fréquence élevée d'une fois par jour est recommandée pour l'irrigation au goutte‐à‐goutte avec de l'eau salée. © 2019 John Wiley & Sons, Ltd.